The Standardization Procedure for Iranian Music (Focusing on the Activities of Alfred Jean Baptiste Lemaire, Aref Qazvini and Ali-Naqi Vaziri) - Moakedi, Saeid; Kashef, Hossein (Journal of History Culture and Art Research, 2018)
The study of Iranian music changes during Qajar and early Pahlavi era, reveals a procedure which indicates the beginning of a kind of standardization. The term “standardization” (matching) seems to be able to state a part of Iranian music change within history. The study of three existing characters of this period of Iran's history (Alfred Jean Baptiste Lemaire, Aref Qazvini and Ali-Naqi Vaziri) raises this question that how standardization (matching) can be followed up in the activities of the aforementioned elites. Having responded to this question, the quality and quantity of Iranian music changes in the intended historical era can be somehow figured out. This study has been conducted through library study using descriptive-analytical method. The findings of this study represent the manner of standardization (matching) in the activities of these three artists. Using notation system and changing the instrument structure, playing Iranian songs with Western instruments, scientific teaching at school and training the apprentices, holding concert and changing the themes and content of some executions and writing music book are among the cases, supposed to be investigated in this paper.